Tindakan Mempekerjakan Anak Di Kota Pekalongan Perspektif Undang-Undang No 13 Tahun 2003 Tentang Ketenagakerjaan Dan Maqashid Syariah - zuhaidah, naila (Al-Hukkam: Journal of Islamic Family Law, 2023)
This writing has problems, namely: how is the practice of employing children in the city of Pekalongan and what is the perspective of Law Number 13 of 2003 concerning Manpower and Maqashid Syariah on the act of employing children in the city of Pekalongan. The aim is to understand and describe the phenomenon of the practice of employing children in the city of Pekalongan and to analyze it in the perspective of Law Number 13 of 2003 concerning Manpower and Maqashid Syariah. The research method used is field research, is descriptive-qualitative. The data sources used are primary and secondary data with data collection techniques through interviews, observations and documentation studies. The results of the study show: First, the act of employing children in Pekalongan City is influenced by community background. In practice, the work they do is included in the non-formal sector with working hours of 4-8 hours per day and wages ranging from 20,000-90,000 per day. The application of Law Number 13 of 2003 concerning Employment on the act of employing children in the City of Pekalongan in the formal sector did not find cases of violations, while in the non-formal sector the Act was unable to reach to apply sanctions because there were no complaints about the impact of employing children in the sector. non-formal. Second, while the practice of employing children in Pekalongan City in the perspective of maqashid sharia can be justified by religious law because its purpose is to fulfill one's needs and is in a condition or situation of urgency.